2009
DOI: 10.1159/000224631
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Maternal Separation Increases Brain-Derived Neurotrophic Factor and Tyrosine Kinase Receptor B Expression in the Descending Pain Modulatory System

Abstract: Neonatal maternal separation (NMS) could trigger long-term changes in the central neuronal responses to nociceptive stimuli in rats. Stress-induced visceral hyperalgesia is closely associated with the dysfunction of descending pain modulatory systems. Brain-derived neurotrophic factor (BDNF) not only has an important role in long-term synaptic plasticity but also in facilitating descending pain. The present study aimed to investigate changes in the expression of BDNF and its receptor tyrosine kinase receptor B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Numerous studies have reported that psychological or chronic stress increases the levels of brain-derived neurotrophic factor (BDNF) expression in the hippocampus, striatum amygdala, and ventral tegmental area in rats [8][9][10] . These reports are consistent with the fact that BDNF is one of the most important endogenous mediators of stress responses in the brain 11) .…”
Section: Introductionsupporting
confidence: 91%
“…Numerous studies have reported that psychological or chronic stress increases the levels of brain-derived neurotrophic factor (BDNF) expression in the hippocampus, striatum amygdala, and ventral tegmental area in rats [8][9][10] . These reports are consistent with the fact that BDNF is one of the most important endogenous mediators of stress responses in the brain 11) .…”
Section: Introductionsupporting
confidence: 91%
“…In fact, BDNF expression was found to be increased on PND 17, approximately 3 days after the last maternal deprivation in frontal cortex and hippocampus, and a single 3 h deprivation on PND 17 did not alter the expression of the neurotrophin in control, as well as in deprived rats [48]. Expression of BDNF and its receptor, tyrosine kinase receptor B, increased in amygdala after neonatal maternal separation [16]. In addition, early deprivation also increased BDNF levels the hippocampus and olfactory bulb [49].…”
Section: Discussionmentioning
confidence: 91%
“…In rodents, several reports indicate that early maternal deprivation affects neurotrophins into adulthood, but results obtained have been contradictory [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Data from our laboratory demonstrated that pharmacological blockade of CB 1 receptors increased formalin-evoked nociceptive behaviour in WKY rats and blockade of FAAH (enzyme catabolising AEA) decreased the hyperalgesia associated with intra-plantar formalinadministration (Rea et al, 2014). In a separate study, adult Wistar rats exposed to MD (maternal deprivation), exhibited higher levels of tyrosine kinase receptor B in the RVM, which is associated with an increase in visceral hypersensitivity to colorectal distension (Chung et al, 2009). The authors demonstrated no effect on the BDNF expression levels in RVM (Chung et al, 2009), although other changes remain to be investigated.…”
Section: Rostral Ventromedial Medullamentioning
confidence: 92%
“…In a separate study, adult Wistar rats exposed to MD (maternal deprivation), exhibited higher levels of tyrosine kinase receptor B in the RVM, which is associated with an increase in visceral hypersensitivity to colorectal distension (Chung et al, 2009). The authors demonstrated no effect on the BDNF expression levels in RVM (Chung et al, 2009), although other changes remain to be investigated. The evidence suggests that the RVM does play a role in hyperalgesia associated with negative affective state.…”
Section: Rostral Ventromedial Medullamentioning
confidence: 98%